Changes in activities of enzymes of glutamate metabolism in rat brain during phosphamidon treatment with reference to behavioral tolerance - RP, Venkateswara; CP, Sanitya; MP, Murali; W, Rajendra (Ethiopian Journal of Science and Technology, 2025)
Organophosphate (OP) pesticides exert their toxic effects by cholinesterase inhibition and the consequent prolongation of the undesirable effects of accumulation of acetylcholine. The signs of toxicity include tremors, convulsions, lachrymation, defecation etc. However, sustained cholinesterase inhibition through sustained sub-acute administration of organophosphates would lead to gradual disappearance of the initial signs of toxicity over time, which is termed as behavioral tolerance. The present study was carried out to examine the activity levels of glutamic acid decarboxylase (GAD), glutamine synthetase and glutamate dehydrogenase (GOH) in different regions of rat brain during acute and sub-acute treatments with the organophosphorus pesticide phosphamidon during different time intervals with due reference to behavioral tolerance. Wistar strain male albino rats ( 150Â±20g) were divided into six groups with six rats in each group /-Acute (1day) and sub-acute (1 day, 7 days, 15 days) doses were administered oy oral intubation, and after specific time intervals different brain regions were isolated for estimation of the enzyme activities. GOH and giutamine synthetase activities were inhibited in almost all regions during different dosing regimen as compared to GAD activity. After acute treatment GAD activity was significantiy inhibited in ail the brain regions except in cerebral cortex where the inhibition was non-significant However, under sub-acute treatment GAD activity showed an elevation in cerebral cortex. cerebellum and striatum, whiie showing a decrease in hippocampus and ponsmedulla. Elevated GAD activity in specific brain reg ions suggests the involvement of GABAergic mechanism during behavioral tolerance to OP compounds Reduced activity levels of GOH suggest iowering of oxidative deamination of glutamate in the brain after acute-dose treatmem.